Existential Dimension of Virtues of Metropolitan Andrei Sheptytsky (Review of: Per amore del suo popolo. La vita eroica del metropolita Andrea Szeptyckyj (1865–1944). Augustyn Babiak. Trapani: Il Pozzo di Giacobbe, 2023. 392 р.) - Гнатів, Андрій; Hnativ, Andrii (Видавництво Львівської політехніки, 2025)
У цій рецензії читач ознайомлюється з книгою Августина Баб’яка “З любов’ю до свого народу. Героїчне життя Митрополита Андрея Шептицького (1865–1944)”, в якій розкривається чеснотливе життя харизматичної постаті в історії української нації та церкви. Дослідник систематично висвітлює духовні сторони митрополита Андрея Шептицького і доносить італійським читачам постать українського громадського і духовного лідера.

The review provides an overview of Augustyn Babyak’s book “For love of his people. The heroic life of Metropolitan Andrey Sheptytsky (1865–1944)” envisaging a virtuous life of apostolic and prophetic voice, a charismatic figure in the history of the Ukrainian nation and church. The researcher shapes heroic virtues of Metropolitan Andrey Sheptytsky’s spirituality providing a more systematic presentation of his historical mission among the Italian audience.
Екзистенційний вимір чеснот митрополита Андрея Шептицького (Рецензія на: Per amore del suo popolo. La vita eroica del metropolita Andrea Szeptyckyj (1865-1944).Augustyn Babiak. Trapani: Il Pozzo di Giacobbe, 2023. 392 р.)
Keywords: віра; надія; любов; кардинальні чесноти; євангельські ради; faith; hope; love; cardinal virtues; evangelical counsels